2007
DOI: 10.1002/clc.20250
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Events in Patients with Chronic Heart Failure (REDUCEhf ) Study Design: Continuous Hemodynamic Monitoring with an Implantable Defibrillator

Abstract: Background The use of implantable cardioverter defibrillators (ICDs) has been proven effective in the prevention of sudden cardiac death (SCD) and constitutes standard of care in appropriate populations. Combining a pressure sensing system with ICD therapy represents the first attempt to provide continuous hemodynamic monitoring using a device previously designed exclusively for SCD protection. Methods REDUCE is a prospective, multicenter, randomized, single‐blind, parallel‐controlled trial designed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Anyway, the real clinical benefit of regularly monitoring congestion in HF outpatients has to be clearly established: a recent study showed a nonsignificant 21% decrease of all HF-related events after 6 month of follow-up in the group receiving fluid status monitoring (by an implanted intrathoracic impedance monitoring device) compared to controls [17]; yet, a retrospective analysis of the time to first HF hospitalization showed a significant risk reduction by 36%. These technologies are now being evaluated in a larger clinical trial [18]. Nonetheless, both American and European guidelines recommend a careful surveillance of the fluid status in the day-to-day management of patients with HF, in order to maintain fluid balance and to avoid volume expansion.…”
Section: When To Assess Pulmonary Congestionmentioning
confidence: 97%
“…Anyway, the real clinical benefit of regularly monitoring congestion in HF outpatients has to be clearly established: a recent study showed a nonsignificant 21% decrease of all HF-related events after 6 month of follow-up in the group receiving fluid status monitoring (by an implanted intrathoracic impedance monitoring device) compared to controls [17]; yet, a retrospective analysis of the time to first HF hospitalization showed a significant risk reduction by 36%. These technologies are now being evaluated in a larger clinical trial [18]. Nonetheless, both American and European guidelines recommend a careful surveillance of the fluid status in the day-to-day management of patients with HF, in order to maintain fluid balance and to avoid volume expansion.…”
Section: When To Assess Pulmonary Congestionmentioning
confidence: 97%
“…Patients were implanted with an IHM-ICD device 6 attached to both a single-standard transvenous ICD lead and a second transvenous hemodynamic pressure sensing lead positioned in the right ventricular outflow tract. The IHM continuously measured and stored right ventricular dP/dt, systolic and diastolic pressures, and an estimate of pulmonary artery diastolic pressure (ePAD).…”
Section: Hemodynamic Monitoringmentioning
confidence: 99%
“…A variety of implantable hemodynamic monitoring devices are also in clinical trials and include stand-alone devices or those coupled with other indicated devices such as implantable cardioverter defibrillators (Table 11.3) [39].…”
Section: Future Monitoring Systemsmentioning
confidence: 99%
“…Implantable hemodynamic monitors (IHM) vary in design, and include devices that continuously measure cardiovascular signals at the right ventricular outflow tract (Chronicle IHM and Chronicle ICD, Medtronic, Inc) with Internet based information systems [8,9,[39][40][41][42], left atrial pressure monitors that allow patient interaction using a handheld device [43,44], and devices that intermittently measure intrapulmonary artery pressures from an implanted device without wires or batteries, powered during interrogation (CardioMEMS, Inc) [45,46]. These devices offer a new paradigm of device-based monitoring and diagnostics that promise to provide a new basis for heart failure medical management.…”
Section: Future Monitoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation